Conceptual exploration for airborne wind energy system for electricity generation in Pulau Perhentian Kecil, Malaysia – MBSE approach - Md Ali, Syaril Azrad; Hassim, Mohamad Iswady (Science Publishing Corporation, 2018)
Renewable energy plant research such as wind energy has been on the rise for the past few decades. The objective of this paper is to do a conceptual exploration of the new type of wind harvesting system known as Airborne Wind Energy System (AWES) to be used in Pulau Perhentian Kecil using Model-Based Systems Engineering Approach (MBSE) where the final selection is chosen using TOPSIS method. There are several types of concept designs to choose from based on their unique mode of operation. The candidate concept designs are from Ampyx Power B.V, Magenn Power, Makani and Altaeros Energies. From the TOPSIS analysis, Ampyx Power B.V has been selected due to its highest fulfilment of the requirements. This exploration into several potential AWES may help solve the deficiency of the current systems and advantageously utilise the suitable geographical factors of Pulau Perhentian Kecil.